ANALISIS PENGARUH PENGEMBANGAN KOMPETENSI SUMBERDAYA APARATUR TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DPRD KABUPATEN KUTAI BARAT - Nur Heni, Marjoni Rachman (PREDIKSI, 2016)
This study aims to determine the competency development program of personnel resources and employee performance. Besides, this study also aims to determine whether there was a significant influence on the development of competence of personnel resources to employee performance at the Parliament Secretariat of West Kutai. The results showed that the empirical rs amounted to 0.631 greater than the theoretical rs of 0.219 for n = 79 at a significance level of 5%. Thus it can be said that there is a significant relationship between the variables of the competence of personnel resources with variable employee performance. The results showed also that the obtained value of 7.136 t-test. The results of these calculations show that the t-count is greater than t-table contained in the table prices are critical student-t for n-2 at the 0.05 level, where t (hit) = 7.136> t (tab) = 1.991 , This means that there is a significant relationship and influence between variable competence development of personnel resources with variable employee performance. Thus it can be said that the formulation of the problem in this study have been answered and the research hypothesis can be received and verified.